Cafetería Amérigo - Brandt Carmigniani, Norman Leslie (2012)
This work consists of a business plan for a cafe located in the northern section of Quito. The plan is quite extensive, and at the same time simple; explains clearly many of the areas to consider when starting a business of this nature, starting with legal, administrative, finishing into a much focused explanation of the gastronomical offer. Studies from an administrative point of view, cover topics such as internal customer relations based…